Dose-related adaptive reconstruction of DMN in isoflurane administration: a study in the rat - Fengru Guo; Yuqin Li; Zhaoxin Jian; Yan Cui; Wenhui Gong; Airui Li; Wei Jing; Peng Xu; Ke Chen; Daqing Guo; Dezhong Yao; Yang Xia (BMC Anesthesiology)
Abstract Background The anesthetic states are accompanied by functional alterations. However, the dose-related adaptive alterations in the higher-order network under anesthesia, e. g. default mode network (DMN), are poorly revealed. Methods We implanted electrodes in brain regions of the rat DMN to acquire local field potentials to investigate the perturbations produced by anesthesia. Relative power spectral density, static functional connectivity (FC), fuzzy entropy of dynamic FC, and topological features were computed from the data. Results The results showed that adaptive reconstruction was induced by isoflurane, exhibiting reduced static and stable long-range FC, and altered topological features. These reconstruction patterns were in a dose-related fashion. Conclusion These results might impart insights into the neural network mechanisms underlying anesthesia and suggest the potential of monitoring the depth of anesthesia based on the parameters of DMN.